Effect of preterm premature rupture of membranes on neurodevelopmental outcome of infants among preterm infants born at Hawassa comprehensive specialized Hospital of Sidama Region, Ethiopia, 2022 - Tegegne, Kaleab Tesfaye; Assefa, Abiyu Ayalew; Geta, Medhin; Zenebe, Andualem; Bagajjo, Wosenyeleh Semeon; Rike, Musie; Weldeyes, Belayneh Feleke (Journal of Advanced Pediatrics and Child Health, 2021)
Objective: To verify whether preterm premature rupture of membranes has effect on neurodevelopmental outcome of Infant among preterm infants born at Hawassa Comprehensive Specialized Hospital of Sidama region, Ethiopia, 2022. Methods and materials: A prospective cohort study design will be conducted for 2 years and 6 months from March 1/2022 to August 30/2024. A total of 12 Midwives. 6 supervisors and 1 pediatric neurologist or psychiatrist will be involved in the data collection process. All preterm infants will be recruited consecutively from preterm infants admitted to neonatal intensive care unit from March 1/2022 to August 30/2022. The preterm infants will be categorized into Exposed group (preterm infants born after preterm PROM) and non-exposed group (preterm infants born after spontaneous preterm labour) and followed until 2 years of age to assess neurodevelopmental outcome of infants The data will be entered into Epidata software and exported to SPSS software for windows version 23. For analysis. Descriptive statistics will be computed. One-way Anova and post hoc comparisons with Scheffe’s procedure will be used X2 test or Fisher’s exact test will be used to compare categorical variables.